A multidimensional comparison of discourse organization in English and Chinese university students' argumentative writing. (2nd May 2013) - Liu, Xinghua; Furneaux, Clare
<x xml:space="preserve">Abstract</x> Three methodological limitations in English‐Chinese contrastive rhetoric research have been identified in previous research, namely: the failure to control for the quality of L1 data; an inference approach to interpreting the relationship between L1 and L2 writing; and a focus on national cultural factors in interpreting rhetorical differences. Addressing these limitations, the current study examined the presence or absence and placement of thesis statement and topic sentences in four sets of argumentative texts produced by three groups of university students. We found that Chinese students tended to favour a direct/deductive approach in their English and Chinese writing, while native English writers typically adopted an indirect/inductive approach. This study argues for a dynamic and ecological interpretation of rhetorical practices in different languages and cultures.